UNPACKING FINANCIAL INCLUSION AS A CATALYST FOR ECONOMIC TRANSFORMATION: EVIDENCE FROM NIGERIA’S BANKING AND MOBILE FINANCE EVOLUTION - Kayode David Kolawole (J-MACC, 2024)
The research study aimed at examining the impact of financial inclusion on economic growth in Nigeria. The study made use of secondary data that was sourced from the central bank statistical bulletin from 1987 to 2021. the study employed Autoregressive Distributed Lag method of analysis to estimate the data. The findings showed that, agent banking, mobile banking, financial services and money management 19.093214, 22.21476, 11.87068 and 2.784910 have significant impact on the gross domestic product. The study concludes that financial inclusion has positive impact on economic growth. The study therefore recommended that, CBN should direct its policy towards increasing the number of agent banks, especially to rural areas of the economy as millions of Nigerians living in rural areas have no access to basic banking services. CBN should collaborate with banks to ensure development of mobile banking applications that can be used on all mobile and telecommunication devices. It is also recommended that apart from directing policies to those inclusion variables that have positive effect on economic growth in Nigeria, government should establish regulatory frameworks that will ensure introduction of low cost and innovative products. Lastly, the government should engage in grass-root education on financial products through SMEs and other channels to increase financial literacy.